Silicon-Organic Hybrid Platform for Photonic Integrated Circuits - Korn, Dietmar (Karlsruhe Series in Photonics and Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2015)
We study the potential of the silicon-organic hybrid (SOH) platform for integrated optics. The unique properties of selected organic materials are added to silicon devices made with CMOS-based processes. We investigate the feasibility of this approach by making prototypes of key components in form of photonic integrated circuits: SOH lasers and SOH modulators are designed, fabricated, post-processed, and characterized. Application scenarios are identified.